Growth of dairy goats in a farm located in Costa Rican Central Valley. - Chacón-Hernández, Pablo (2015)
The main objective of this research was to evaluate the growth on dairy goats from birth to the breeding age. The experiment was carried out at the University of Costa Rica’s Alfredo Volio Mata Experimental Station, located at 9°55’10’’ N, and 83°57’20’’ W. From December 2013 to August 2014, every born goats were weekly weighed until the weaning age of 90 days after birth, when the same animals were weighed every fortnight until the end of the experimental period. Besides, these animals were fed with milk (20% of live weight) until weaning, then their feed was based on forage and a balanced grain mix according to their nutritional needs. During the experimental period, management, housing, and health followed animal welfare principles, to guarantee the optimum growth of kids. According to the analyzed data, average birth weight and daily weight gain was 4.27 kg and 90 g, respectively; also, it took an average of 286 days for the animals to reach a live weight of 30 kg, the minimum breeding weight. Based on the analyzed information, a higher energy intake is necessary to increase the average daily weight gain, reduce the breeding age and the adult live weight in goats.